PENGARUH KEBERADAAN PANGKALAN PENDARATAN IKAN (PPI) SAIJAAN KOTABARU TERHADAP PENDAPATAN PENGUSAHA PERIKANAN DI KECAMATAN PULAU LAUT UTARA KABUPATEN KOTABARU PROVINSI KALIMANTAN SELATAN - Syahruddin Syahruddin; Idiannor Mahyudin; Emmy Sri Mahreda (Fish Scientiae, 2019)
Fish landing base (PPI) is a container that can support development and the development of a better fishery. Accordence with the increasing number of fishing vessels that enter the territory Kotabaru, either the ships from itself or the ships that come from the outside area. Making the existence of the PPI Saijaan Kotabaru a medium which accommodates fishery activities to make a direct relevance relationship of up river and downstream activities. This research was conducted: identifying facilities, condition sand function of the PPI Saijaan Kotabaru; Analyzing changes in the income of entrepreneur fishery before and after the PPI Saijaan Kotabaru in District Stagen Kotabaru; Formulating a strategy of economic development of the PPI Saijaan Kotabaruas an area of fisheries. Analysis Technique of the research uses qualitative and quantitative method with descriptive approach. The results obtained that the basic, functional and additional facilities of the PPI Saijaan Kotabaru have been fulfilled by 90 % and have not been fulfilled by 10 % thatneed to be developed. Condition and function facilities of the PPI Saijaan Kotabaru, is only 90 % facilities are function optimally and 10 % is not function optimally.Wilcoxon test results in Statistics Test, shows that value of Wilcoxon test pvalue is 0.003 (< 0.05), then Ho is rejected and H1 is accepted, meaning that there is avery significant difference from the increased income of entrepreneur fishery afterthe construction of the PPI Saijaan Kotabaru as well. The results of the value to external factors (EFAS) is = 2.85, while for internal factors (IFAS) is = 2.55. So the value of EFAS >IFAS value, then a qualitative activity and capacity of existing facilities of the PPI Saijaan Kotabaru still very likely to be developed.